(untitled) (Journal of the College of Basic Education, 2022)
The research aims to study the overlap of the purpose of praise in the lament, but the value of the elegy poem depends on what it contains of strong emotion, and what is contained in it of sad words that burn the heart, as well as the way in which it is formulated. If the poet is able to describe it, and focus on explaining his feelings, the heat of emotion, and highlighting that with his poetry, then the poem is loaded with a sincere sense of saying. The poet who can reconcile the meaning with the purpose to which the poem came out is a poet who has excelled in his poem, and the feeling remains vague in the poet’s soul, and it becomes clear to him only after it is formed in an image. And there are those who worked to benefit from death and praise for the purpose of obtaining something that he himself hopes for, and this is what we will show in the pages eligible